The Implementation of Financial Management and Digital Marketing for Urban Village MSMEs in Enhancing Business Competitiveness - Dede Dahlan; Wahyu Anugrah Manippi; Iwan Subandi; Andi Andi; Rahmat Jaya (International Journal of Community Service (IJCS), 2026)
Aprilianti, D., Agustian, A., & Narimawati, U. (2025). Adoption and Use of Digital Marketing Tools Among Food and Beverage MSMEs in Gen Z. Jurnal Ilmiah Manajemen Kesatuan, 13(4), 2889–2908. https://doi.org/10.37641/jimkes.v13i4.3687 Creswell, J. W. (2021). Research design: Qualitative, quantitative, and mixed methods approaches (5th ed.). SAGE Publications. Fujianti, L., Masri, I., Kasim, E., & Aditia, D. P. (2025). INTRODUCTION TO WARUNG APPLICATION-BASED DIGITAL ACCOUNTING FOR IMPROVING THE EFFICIENCY OF FINANCIAL RECORD-KEEPING OF MSMES IN CURUG BOGOR VILLAGE. Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 9(3), 1113–1125. https://doi.org/10.32832/abdidos.v9i3.2893 Hadi, D. P., Sumastuti, E., Indriasari, I., & Fathurachman, C. (2025). Strategies for improving ASEAN MSME competitiveness by applying digital marketing, business management quality and crowdfunding by applying product innovation and operational efficiency as intervening variables. Edelweiss Applied Science and Technology, 9(6), 2870–2885. https://doi.org/10.55214/25768484.v9i6.8500 Itua, A. T., AKOGWU, D. P. R., & Senkoya, D. M. A. (2025). The Role of Cultural Sensitivity in Digital Marketing Effectiveness and Platform Engagement. International Journal of Research and Scientific Innovation, 12(10), 2740–2747. https://doi.org/10.51244/IJRSI.2025.1210000234 Muhammad Mubushar, Fahmeed Idrees, & Muhammad Ali Mufti. (2025). Innovation Capability as a Mediator of Financial Resources, Digital Marketing Capability, Entrepreneurial Orientation, and Start-Up Growth. Contemporary Issues in Social Sciences and Management Practices, 4(3), 143–154. https://doi.org/10.61503/cissmp.v4i3.337 Murari, D. K. (2025). A Study on Adoption of Digital Technologies by the MSMEs. INTERNATIONAL JOURNAL OF SCIENTIFIC RESEARCH IN ENGINEERING AND MANAGEMENT, 09(07), 1–9. https://doi.org/10.55041/IJSREM51165 Nugraha, F. A., Ahmatang, A., Ali, H., Lukiyanto, K., & Tawil, M. R. (2025). Influence Of External and Internal Factors On The Performance Of MSMEs In Indonesia. Maneggio, 2(1), 237–245. https://doi.org/10.62872/5wtkae52 Sugiyono. (2019). Metode penelitian pendidikan: Pendekatan kuantitatif, kualitatif, dan R&D. Alfabeta. Suvittawat, A. (2026). Drivers of Farmers’ Adoption Intention for Soil Nutrient Analyzers: Roles of Awareness, Perceived Usefulness, and Ease of Use. Agriculture, 16(3), 390. https://doi.org/10.3390/agriculture16030390